One-Hand Engineering Effectiveness to the Reduction of the Number of Bloodage in Third-Three Phase of Certificate Mother in Maulidya Husada Clinic, Karangploso Sub-District, Malang District - Herwati Herwati; Rahmania Ambarika; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The maternal mortality rate in Indonesia in 2015 was 305 out of 100,000 live births according to the Ministry of Health of the Republic of Indonesia (Kemenkes). Based on data from the Ministry of Health's Center for Health and Information (2014), the main causes of maternal mortality from 2010-2013 were bleeding (30.3% in 2013) and hypertension (27.1% in 2013). Postpartum hemorrhage is bleeding that occurs after delivery (delivery), as much as 500 ml in vaginal delivery or more than 1000 ml in cesarean section. This study aims to determine the effectiveness of the one-hand technique in reducing the amount of bleeding compared to the two-hand technique that has been used in third-stage active management. This study is an experimental quantitative study to compare the one-hand technique in third-stage active management versus the two-hand technique. The population was taken from all pregnant women who gave birth in the delivery room of KRI Maulidya Husada within three months. The number of samples in this study were 36 people, namely: 18 people using the one-hand technique that met the inclusion criteria and 18 people using the two hand technique who met the inclusion criteria. In this study, it is known that almost all respondents with spontaneous labor who were given the one-hand technique experienced bleeding less than 250cc, namely 61% and the two-hand technique treatment experienced bleeding more than 250cc, namely 39%